2017
DOI: 10.1515/pjct-2017-0067
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite as the catalyst in oxidation of limonene with hydrogen peroxide and in isomerization of limonene

Abstract: In our studies montmorillonite (MMT) was used as the heterogeneous, natural catalyst. This material was previously prepared by bentonite purifi cation with help of the sedimentation method. The obtained catalyst was characterized by: XRD, SEM, BET and EDX. Catalytic tests with montmorillonite as the catalyst were performed with the natural terpene -R-(+)-limonene. This compound was oxidized with hydrogen peroxide and, moreover, in the separate process it was also isomerized. As the main products of limonene ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition to that, more inorganic microporous supports such as TS-1 and Ti-SBA-15 tested in [72]. This work highlights a remarkable loss of selectivity with the raise of temperature, obtaining the best selectivity to 1,2-limonene oxide at 0 • C. Malko et al [77], used montmorillonite as catalyst for the oxidation and isomerization reactions of R-(+)-limonene. Once, the catalyst was obtained by a purification process of bentonite using a sedimentation method, it was followed to evaluate the catalytic activity.…”
Section: With Fresh Catalyst 75mentioning
confidence: 90%
“…In addition to that, more inorganic microporous supports such as TS-1 and Ti-SBA-15 tested in [72]. This work highlights a remarkable loss of selectivity with the raise of temperature, obtaining the best selectivity to 1,2-limonene oxide at 0 • C. Malko et al [77], used montmorillonite as catalyst for the oxidation and isomerization reactions of R-(+)-limonene. Once, the catalyst was obtained by a purification process of bentonite using a sedimentation method, it was followed to evaluate the catalytic activity.…”
Section: With Fresh Catalyst 75mentioning
confidence: 90%
“…Beside the current applications of these natural and renewable products in the fields of fragrances and flavors in cosmetic and food industry [1], their transformation into value-added products via sustainable processes is of highest economical interest. Oxidation, epoxidation, hydroformylation, hydrogenation, isomerization, rearrangement of terpenes, most of these catalytic transformations taking advantage of the presence of at least one carbon-carbon double bond in the initial molecule have been successfully achieved [4][5][6][7][8]. Olefin metathesis is also a clean catalytic transformation with high potential for direct modification of unsaturated natural products that has been applied to fatty acid derivatives [9,10], phenylpropanoids [11] REVISED MANUSCRIPT 2 and terpenes [12] mainly in the presence of ruthenium catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…A more advantageous scheme for the production of the diepoxide seems to be in the presence of a catalyst of natural origin-montmorillonite. The preliminary study over this porous material was presented by Malko et al [16] and showed the possibility to obtain the diepoxide with the selectivity of about 48 mol%, but this work needs further development by studying the influence of other appropriate parameters.…”
Section: Introductionmentioning
confidence: 99%